2012
DOI: 10.17221/288/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maillard reaction on reducing power of malts and beers

Abstract: AbstractČechovská L., Konečný M., Velíšek J., Cejpek K. (2012): Effect of Maillard reaction on reducing power of malts and beers. Czech J. Food Sci., 30: 548-556.HPLC with amperometric detection was used to evaluate the reducing power of 23 beers and aqueous extracts of 17 barley malts. While brew pale malts were only slightly higher in electrochemical reducing capacity than natural barleys (about 1.3 g BHAE/kg), caramel malts with the colour of 60-450°EBC showed 7.5-17.2 g BHAE/kg. The superior reducing power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Around 80% of the phenolic compounds identified in beer is derived from malt, while the remaining 20% comes from hops (De Keukeleire ; Quifer‐Rada and others ). Moreover, malt can contribute to about 95% and 86% of the antioxidant capacity of dark and pale beers, respectively (Čechovská and others ), while hopping did not significantly affect the phenolic content or the antioxidant activity of beer (Leitao and others ). Accordingly, malt can be described as the principal source of antioxidants in beer.…”
Section: Modifications Through Malting and Roastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 80% of the phenolic compounds identified in beer is derived from malt, while the remaining 20% comes from hops (De Keukeleire ; Quifer‐Rada and others ). Moreover, malt can contribute to about 95% and 86% of the antioxidant capacity of dark and pale beers, respectively (Čechovská and others ), while hopping did not significantly affect the phenolic content or the antioxidant activity of beer (Leitao and others ). Accordingly, malt can be described as the principal source of antioxidants in beer.…”
Section: Modifications Through Malting and Roastingmentioning
confidence: 99%
“…It was reported that the antioxidant capacity of malt can increase during kilning and roasting, not only because modification or release of phenolic compounds, but also due to the development of reductones and MRPs through the Maillard reaction (Maillard and others ; Woffenden and others ; Samaras and others ; Vanderhaegen and others ; Inns and others ). Herein, MRPs have been identified as the major contributors to the antioxidant activity of roasted malts (Coghe and others , ; Samaras and others ), with a positive influence on the maintenance and development of malt reducing properties (Čechovská and others ).…”
Section: Antioxidant Potential Of Maltmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 70-80% of the phenolic compounds present in beer are derived from malt, while the remaining 30-20% come from hops [5,6]. Moreover, malt can contribute to around 95% and 86% of the antioxidant capacity of dark and pale beers, respectively [7], while hopping did not affect significantly the antioxidant activity of beer [8].…”
Section: Introductionmentioning
confidence: 95%
“…pale malt delivers around 80-85% of polyphenols to beer, whereas dark speciality malt delivers approx. 95%), whereas hops contribute only a minor fraction of the total beer polyphenols (88)(89)(90). Melanoidins and reductones (intermediates of Maillard reactions) are present in all types of malt, however, in particular in dark speciality malts as they are mostly formed during the roasting process through intensive heating.…”
Section: -Methylpropanalmentioning
confidence: 99%